THE EFFECTS OF THE ABUSE EXPERIENCED BY DAVID CHARACTER’S IN DAVID PELZER’S A CHILD ALLED AND THE LOST BOY - Adeline Grace Marianne Litaay (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2018)
The study discusses the effects of the abuse experienced by David’s character in David Pelzer’s A Child Called It and The Lost Boy. The theory applied is psychological theory about child abuse and the research method applied is qualitative research by Blaxter. Based on the research, it is found that the effects of the above abuse that David experienced were flashback through nightmares, the feeling of insecure and frightened, low self esteem and inferior feeling, difficulties to trust others and develop friendliness, and deteriotating school performance. Besides, David had deviant actions (stealing), obstacles to understand and receive love and/or properness, and emotional control disorder.